The influence of family factors and the COVID-19 pandemic on the nutritional status of children under five years - Milah, Ana Samiatul; Rohita, Tita (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2025)
This study investigates the intricate relationship between nutritional intake patterns, parenting practices, hygiene habits, and access to health services in influencing the nutritional status of children under five years old, particularly within the context of the ongoing COVID-19 pandemic in Indonesia. Recognizing that malnutrition remains a significant health concern, exacerbated by the pandemic's impact on social order and healthcare access, this research underscores the crucial role of maternal behavior and family environment in shaping children's health outcomes. The study draws upon existing literature highlighting the consequences of malnutrition, including stunting, wasting, and increased susceptibility to infectious diseases. Furthermore, it acknowledges the effectiveness of the Positive Deviance/Hearth Specialist approach in addressing malnutrition through community-based solutions. The discussion of research findings from Baregbeg Village, Ciamis Regency in 2021, which indicated a high prevalence of undernutrition (58.1%), reinforces the urgency of comprehensive interventions. The study emphasizes that addressing malnutrition requires a multi-faceted approach involving not only healthcare professionals but also parents, families, community leaders, and the government, particularly in promoting clean and healthy living behaviors (CHLB) as a preventive measure against both malnutrition and COVID-19. The conclusion stresses the importance of disciplined adherence to health protocols and collaborative efforts among all societal elements to combat the pandemic and improve the nutritional well-being of the nation's children.